Analysis of the Impact of Fly Ash on Environmental Pollution (Case Study of Pulp and Paper Pangkalan Kerinci) - Resfianto Resfianto; Ridwan Manda Putra; Syahril Nedi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
The accumulation of fly ash in large quantities will cause problems for the environment, such as air and water pollution and a decrease in the quality of ecosystems containing Ni, V, As, Be, Cd, Ba, Cr, Cu, Mo, Zn, Pb, Se and Ra which can affect groundwater quality and human health. This study aims to analyze the impact of waste generated from the Pulp and Paper on the environment around the industry. The data obtained is in the form of primary data from the results of the Toxicity Characteristic Leaching Procedure (TCLP) test and direct observation in the field to identify environmental conditions around the landfill, while TLCP laboratory analysis was carried out to determine the toxic characteristics of TLCP in fly ash from the Pulp and Paper BaseKerinci. The TCLP test results for fly ash the analyzed waste Fly ash produced from the pulp and paper is suitable for use with fly ash class F2+A12O3+Fe2O3 content of 75.19%. Utilization of fly ash can be an effort to reduce the impact of fly ash on environmental pollution. The waste produced by pulp and paper obtains a metal value below the quality standard so that it does not have a negative impact on the surrounding environment.